Production and selection of accessions of Opuntia spp. with resistance to false carmine cochineal - Batista, Mateus Costa; Nascimento, Ronaldo do; Almeida, Isaias Vitorino Batista de; Torreão Villarim de Medeiros, Leonardo; Thyago Aires Souza, José; de Oliveira Santos, João Paulo; de Almeida Cartaxo, Paulo Henrique; Rayan Eraldo Souza Araújo, José (Comunicata Scientiae, 2022)
The genetic improvement program for Opuntia spp. aims to select new genotypes to meet the demands of rural producers in the Brazilian Semiarid region and to expand the genetic base of the crop. The aim of this study was to select accessions of Opuntia spp. with foraging potential and resistance to false cochineal carmine. The research was carried out at the Active Germplasm Bank (BAG) of Opuntia spp. of Paraíba Company Research, Rural Extension and Land Regularization (EMPAER), Pendência Experimental Station, Soledade, Paraíba, Brazil. Accessions were cultivated in rainfed and evaluated in August 2019, 12 months after the implementation of the BAG. The measurement of the Total Green Mass weight of the plants of 121 accessions of the BAG was carried out and the productivity (ton/ha-1) was estimated in a dense cultivation of 100 thousand plants/ha-1. The accessions of Opuntia spp. nº 10, 110, 115 and 119 have growing potential in the Brazilian Semiarid region, as a function of productivity (532.6, 118, 164 and 481 tons/ha-1, respectively) and resistance to false carmine cochineal, in addition to genetic divergence (specific agronomic characteristics) in relation to currently cultivated varieties.